2017
DOI: 10.1177/0033294116688890
|View full text |Cite
|
Sign up to set email alerts
|

The HEXACO Model of Personality and Risky Driving Behavior

Abstract: This research tested the association between the HEXACO personality model and risky driving behavior as well as the predictive power of the HEXACO model in explaining risky driving behavior compared with the Big Five model. In Sample 1, 227 undergraduate students completed measures of the HEXACO personality model, the Big Five model, and driving aggression. In Sample 2, 244 community respondents completed measures of the HEXACO personality model, the Big Five model, and driving styles. Results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…Extraversion is associated with energy, dominance, assertiveness, and ambition (Costa and McCrae, 1992; Hurtz and Donovan, 2000). Extroverted individuals are more likely to seek excitement, and stimulation and be positive and optimistic (Burtăverde et al , 2017). Thus, extraversion might lead a person to engage in more innovative intrapreneurial efforts than those who choose more traditional jobs (Farrukh et al , 2016; Sinha and Srivastava, 2013).…”
Section: Theoretical Background and Study Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraversion is associated with energy, dominance, assertiveness, and ambition (Costa and McCrae, 1992; Hurtz and Donovan, 2000). Extroverted individuals are more likely to seek excitement, and stimulation and be positive and optimistic (Burtăverde et al , 2017). Thus, extraversion might lead a person to engage in more innovative intrapreneurial efforts than those who choose more traditional jobs (Farrukh et al , 2016; Sinha and Srivastava, 2013).…”
Section: Theoretical Background and Study Hypothesesmentioning
confidence: 99%
“…Prior studies have considered conscientiousness as the primary motivational component (Zhao et al , 2010). It is characterized as work motivation, achievement motivation, goal orientation, self-control, organizing, and planning behavior (Burtăverde et al , 2017; Costa and McCrae, 1992; Hurtz and Donovan, 2000). Thus, conscientious people who are goal orientated, motivated, and willing to persevere would be attracted to an intrapreneurial career over more traditional types of work (Farrukh et al , 2016; Sinha and Srivastava, 2013).…”
Section: Theoretical Background and Study Hypothesesmentioning
confidence: 99%
“…Furthermore, a small number of studies have reported that neuroticism had a significant negative relationship with RDBs. 16,40,43 Perhaps this dissimilar finding was due to the mean age of participants in these studies, which mainly consisted of young adults. Our subgroup analysis indicated that in the >40 years old age group RDBs were positively related to neuroticism.…”
Section: Discussionmentioning
confidence: 86%
“…These studies have reported that low levels of agreeableness can predict high levels of risky driving outcomes, including crashes. 15-17,19,21,32,35-37,40,42-43 In contrast, research by Brown et al (2016) and Sween et al (2017) found no significant relationships between Agreeableness and RDBs. 20,41 There may be a number of reasons for these disparate findings.…”
Section: Discussionmentioning
confidence: 86%
“…Risky social behaviors. Taking into account that some other broad personality factors, such as Conscientiousness and Honesty-Humility, refer to what degree an individual complies with social norms, values, and principles (e.g., Burtȃverde, Chraif, Anit ßei, & Dumitru, 2017;Schmitt, 2004), we aimed to select criteria that offer information about the extent to which an individual interacts with his or her environment in a maladaptive way. We chose the following four indicators: short mating orientation, previous socio-sexual behavior, safety-related risk activities, and traffic fines.…”
mentioning
confidence: 99%